A Bubble‐Derived Strategy to Prepare Multiple Graphene‐Based Porous Materials. (3rd April 2018) - Zhang, Rujing; Hu, Ruirui; Li, Xinming; Zhen, Zhen; Xu, Zhenhua; Li, Na; He, Limin; Zhu, Hongwei
Abstract: Graphene‐based porous structures have triggered tremendous attention due to their promising application in many fields. Recent progress has yielded structures with stochastic porous networks, which limit their controllability and potential performance. It still remains a big challenge for the scalable production to integrate the 2D building block into engineered porous architectures in multidimensions. Here, a versatile technique based on soft bubble templating and fixation by freezing is described to fabricate 3D bubble‐derived graphene foams (BGFs) and 2D bubble‐derived graphene porous membranes (BGPMs). These light‐weight novel structures are carefully tuned. The BGFs show high adsorption capabilities for organic solvents and good recovery in structural deformation. Furthermore, applications of BGFs and BGPMs in strain sensors for wearable devices are discussed, working as a combined system which can both detect the compressive and tensile deformation. This technique can be extended to assemble other nanomaterials as building blocks into macroscopic configurations. Abstract : A versatile technique based on soft bubble templating and fixation by freezing is utilized for the preparation of 3D lightweight graphene foams. The architecture is well aligned and engineered. Furthermore, the method can be expanded to fabricate 2D large‐area porous graphene membranes.